Almost Quasi Continuity and Weak Quasi Continuity for Multifunctions Between an Ideal Topological Space and a Bitopological Space (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces four classes of continuous multifunctions defined from an ideal topological space into a bitopological space, namely upper almost quasi $τ^\star(σ_1,σ_2)$-continuousmultifunctions, lower almost quasi $τ^\star(σ_1,σ_2)$-continuous multifunctions, upper weakly quasi $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower weakly quasi $τ^\star(σ_1,σ_2)$-continuous multifunctions. Moreover, several characterizations of upper almost quasi $τ^\star(σ_1,σ_2)$-continuous multifunctions, lower almost quasi $τ^\star(σ_1,σ_2)$-continuous multifunctions, upper weakly quasi $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower weakly quasi $τ^\star(σ_1,σ_2)$-continuous multifunctions are established. Furthermore, the relationships between almost quasi $τ^\star(σ_1,σ_2)$-continuity and weak quasi $τ^\star(σ_1,σ_2)$-continuity are discussed.